2017
DOI: 10.6113/jpe.2017.17.1.96
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Modular Multilevel Converter Topology with an Improved Nearest Level Modulation Method

Abstract: In this paper, a hybrid modular multilevel converter (MMC) topology with an improved nearest level modulation method is proposed for medium-voltage high-power applications. The arm of the proposed topology contains N series connected half-bridge submodules (HBSMs), one full-bridge submodule (FBSM) and an inductor. By exploiting the FBSM, half-level voltages are obtained in the arm voltages. Therefore, an output voltage with a 2N+1 level number can be generated. Moreover, the total level number of the inserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The results show a significantly improved THD, however, the study does not discuss applying the method to a reduced number of levels (less than 21). After a precise review of the literature, it was found that few studies have been conducted on the NLC method applied to the TCHB inverter compared to MMC [22][23][24][25] and asymmetrical CHB MLI [7,21]; Therefore, this paper focuses on applying the NLC method to a 13 level A-TCHB inverter with a DC voltage ratio 1: 2 between two TCHB cells. The method operates at the fundamental frequency and can be extended to any number of levels.…”
Section: Issn: 2088-8694 mentioning
confidence: 99%
“…The results show a significantly improved THD, however, the study does not discuss applying the method to a reduced number of levels (less than 21). After a precise review of the literature, it was found that few studies have been conducted on the NLC method applied to the TCHB inverter compared to MMC [22][23][24][25] and asymmetrical CHB MLI [7,21]; Therefore, this paper focuses on applying the NLC method to a 13 level A-TCHB inverter with a DC voltage ratio 1: 2 between two TCHB cells. The method operates at the fundamental frequency and can be extended to any number of levels.…”
Section: Issn: 2088-8694 mentioning
confidence: 99%
“…There are lots of high frequency components in arm currents and circulating currents and this will increase the current stress, power loss, and electromagnetic interference of devices. Although the high‐frequency currents generated by pulse voltage can be suppressed by increasing the arm inductance, this will bring other problems such as a large inductor size and circuit dynamic poor performance . A hybrid topology of MMC is able to increase the level number of the output voltage and keeps the total number of inserted SMs unchanged …”
Section: Introductionmentioning
confidence: 99%
“…Although the high-frequency currents generated by pulse voltage can be suppressed by increasing the arm inductance, this will bring other problems such as a large inductor size and circuit dynamic poor performance. 25 A hybrid topology of MMC is able to increase the level number of the output voltage and keeps the total number of inserted SMs unchanged. 25 However, this makes MMC topology complicated and weakens the modularity of MMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu bağlamda, MÇD'ler için faz-kaydırmalı taşıyıcı DGM, UVM ve ESM metotlarının çıkış gerilim ve akım harmonik içerikleri bakımından farklı durum çalışmaları altında hem simülasyon ortamında hem de alanda programlanabilir kapı dizisi (Field Programmable Gate Array-FPGA) kartı kullanılarak gerçek bir platform üzerinde deneysel karşılaştırılmaları yapılmıştır [18]. Yarımköprü ve tam-köprü alt modüllerden oluşan hibrit MÇD topolojisi için iyileştirilmiş ESM stratejisi simülasyon ve deneysel çalışma ile gerçekleştirilerek önerilmiştir [19]. ESM tekniğinin 6-seviyeli MÇD üzerinde uygulanması hem deneysel olarak hem de simülasyon ortamında gösterilmiştir [20].…”
unclassified